Analisis Kepemimpinan, Pendidikan dan Kemampuan Kerja Terhadap Kinerja Pegawai pada Kantor Dinas Kesehatan Kabupaten Langkat - Amalia, Ira; Kholik, Kholilul (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to analyze whether leadership, education, and skills simultaneously and significantly affect employee performance. The research approach used in this study is associative and quantitative. The population in this study is the employees of the Langkat Regency Health Office, totaling 92 people. The sampling technique used is a saturated sample in which the entire population is used as the sample. The instrument for data collection in this research is a questionnaire. The data analysis technique used in this study is multiple linear regression. The research results show that leadership has an effect on performance, as evidenced by the t-count value of 3.615 > the t-table value of 1.987 with a significance value of 0.000 < 0.05. The results of this study indicate that education does not have a significant effect on employee performance, as evidenced by the t-count value of 1.966 < the t-table value of 1.987 with a significance value of 0.052 > 0.05. The results of this study show that work ability has a positive and significant effect on employee performance, as evidenced by the t-count value of 7.035 > the t-table value of 1.987 with a significance value of 0.000 < 0.05. The results of this study explain that motivation, job satisfaction, and commitment have a positive and significant effect simultaneously on employee performance, as evidenced by the multiple linear regression analysis with an F-count value of 53.043 > the F-table value of 2.71 and a significance value of 0.000 < 0.05.